2016
DOI: 10.1039/c5cs00440c
|View full text |Cite
|
Sign up to set email alerts
|

Spectral pre and post processing for infrared and Raman spectroscopy of biological tissues and cells

Abstract: Vibrational Spectroscopy, both infrared absorption and Raman spectroscopy, have attracted increasing attention for biomedical applications, from in vivo and ex vivo disease diagnostics and screening, to in vitro screening of therapeutics. There remain, however, many challenges related to the accuracy of analysis of physically and chemically inhomogeneous samples, across heterogeneous sample sets. Data preprocessing is required to deal with variations in instrumental responses and intrinsic spectral backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 100 publications
(211 reference statements)
0
112
0
Order By: Relevance
“…The IR spectrum contains rich and specific information about the molecular composition of the human serum which, coupled to advanced multivariate analysis tools, could deliver accurate diagnostics. Recent systematic studies have demonstrated the potential of IR serum based diagnosis with different data mining approaches such as Principal Components Analysis (PCA), PCA coupled to Linear Discriminant Analysis (PCA-LDA), Random Forest or Support Vector Machine (SVM) [26][27][28][29][30] . However, the development of spectroscopic technologies with medical perspectives needs to align with clinical requirements to enable clinical translation of these promising technologies 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The IR spectrum contains rich and specific information about the molecular composition of the human serum which, coupled to advanced multivariate analysis tools, could deliver accurate diagnostics. Recent systematic studies have demonstrated the potential of IR serum based diagnosis with different data mining approaches such as Principal Components Analysis (PCA), PCA coupled to Linear Discriminant Analysis (PCA-LDA), Random Forest or Support Vector Machine (SVM) [26][27][28][29][30] . However, the development of spectroscopic technologies with medical perspectives needs to align with clinical requirements to enable clinical translation of these promising technologies 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Transflection IR, in comparison, uses cheap MirrIR slides that are easier to handle. [39] As the beam passes through the sample twice, transflection IR also results in better signal-to-noise, and a reduced acquisition time can be used to achieve the same quality spectra as with transmission IR. [58] Alternatively, this means for transflection IR can use samples with less thickness can be used.…”
Section: Infrared Spectroscopy For Monitoring Drug-cell Interactionmentioning
confidence: 99%
“…The primary disadvantage of transmission IR is that it generally requires high cost substrates such as calcium fluoride, which are also brittle, and therefore care must be taken when handling them. [39] The cost of the substrate would make translating this technique into a HTS platform difficult as a result of the cost involved. However, if substrates could be reused this would reduce the consumable cost.…”
Section: Infrared Spectroscopy For Monitoring Drug-cell Interactionmentioning
confidence: 99%
See 2 more Smart Citations